Institutional Development of Child Care in Armenia: Structural-Organizational, or Value-Systemic Approach? - Antonyan, Mira (Journal of Sociology: Bulletin of Yerevan University, 2021)
Discussions on the transformation of social issues, particularly the lack of a viable approach to responding to the shortcomings of family care, from the Soviet era are still relevant thirty years later. In particular, education, care and protection of children in institutions and to accommodate changing practices used in the process of forming a latent attitude system based on children’s rights, non-formal resistance discussion interesting to understand what potential they have undertaken an organizational structural transformation of values desired to bring about change. Will these transformations be able to influence the changing practices of helping children in need outside of the family environment something that continues to be the subject of unspoken agreement between the three parent-decision-making parties today, ignoring children’s rights and interests?